Association between cytomegalovirus seropositivity and Type 2 diabetes is explained by age and other demographic characteristics: the National Health and Nutrition Examination Survey. Issue 12 (3rd August 2018) - Schmidt, L.; Nelson, H. H.; Thyagarajan, B.; Hunter‐Schlichting, D.; Pankow, J. S.; Capistrant, B.; Prizment, A. E.
Abstract: Aims: To assess the association between cytomegalovirus and Type 2 diabetes among 6664 participants from the National Health and Nutrition Examination Survey. Methods: We used existing data from adults aged 20–49 years who participated in the National Health and Nutrition Examination Survey from 1999 to 2004. Cytomegalovirus status was determined using cytomegalovirus‐specific immunoglobulin G antibodies. Prevalent Type 2 diabetes was assessed through self‐report or a plasma fasting glucose of ≥7 mmol/l. Logistic regression models were used to evaluate the association between Type 2 diabetes and cytomegalovirus seropositivity after adjustment for age, gender, race/ethnicity, smoking status, education, BMI and physical activity. Results: In a univariate model, the crude odds of Type 2 diabetes were 47% higher in those who were cytomegalovirus‐seropositive vs cytomegalovirus‐seronegative. The association was attenuated and no longer significant after adjustment for age and other covariates: the odds ratio for diabetes was 1.09 (95% CI 0.71 to 1.66) for cytomegalovirus‐seropositive vs ‐seronegative individuals. Conclusions: Our study suggests that the association between cytomegalovirus and Type 2 diabetes is explained by age and other risk factors for diabetes. What's new?: Despite a plausible biological mechanism, there is limited epidemiological research investigating cytomegalovirus (CMV) and Type 2 diabetes. Using the National Health and Nutrition Examination Survey, we found a 47% increased prevalence odds of Type 2 diabetes associated with CMV infection. Consistent with previous cross‐sectional studies, the present analysis in a large, nationally representative sample of US adults suggests that the association between CMV and diabetes is most likely explained by confounding with age and other demographic and lifestyle characteristics. Although there is no evidence that CMV increases the risk of Type 2 diabetes among middle‐aged individuals, future research should address whether CMV infection complicates the course of the disease, especially when the patients become older.